Pretreatment prostate-specific antigen (PSA) velocity and doubling time are associated with outcome but neither improves prediction of outcome beyond pretreatment PSA alone in patients treated with radical prostatectomy. - O'Brien, M; Cronin, A; Fearn, P; Smith, B; Stasi, J; Guillonneau, B; Scardino, P; Eastham, J; Vickers, A; Lilja, H (2009)
PURPOSE: Controversy exists as to whether current pretreatment prostate-specific antigen (PSA) dynamics enhance outcome prediction in patients undergoing treatment for prostate cancer. We assessed whether pretreatment PSA velocity (PSAV) or doubling time (PSADT) predicted outcome in men undergoing radical prostatectomy and whether any definition enhanced accuracy of an outcome prediction model. PATIENTS AND METHODS: The cohort included 2,938 patients with two or more PSA values before radical prostatectomy. Biochemical recurrence (BCR) occurred in 384 patients, and metastases occurred in 63 patients. Median follow-up for patients without BCR was 2.1 years. We used univariate Cox proportional hazards regression to evaluate associations between published definitions of PSADT and PSAV with BCR and metastasis. Predictive accuracy was assessed using the concordance index. RESULTS: On univariate analysis, two of 12 PSADT and four of 10 PSAV definitions were univariately associated with both BCR and metastasis (P < .05). One PSADT and one PSAV definition had a higher predictive accuracy for BCR over PSA alone, and four PSAV definitions improved prediction of metastasis. However, the improvements in predictive accuracy were small, associated with wide CIs, and markedly reduced if additional predictors of stage and grade were included alongside PSA. Modeling with random variables suggests that similar results would be expected by chance. CONCLUSION We found no clear evidence that any definition of PSA dynamics substantially enhances the predictive accuracy of a single pretreatment PSA alone.